1998
DOI: 10.1074/jbc.273.38.24470
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Condensation Is Not Associated with Apoptosis

Abstract: Apoptosis plays an important role in the survival of an organism, and substantial work has been done to understand the signaling pathways that regulate this process. Characteristic changes in chromatin organization accompany apoptosis and are routinely used as markers for cell death. We have examined the organization of chromatin in apoptotic PC12 and HeLa cells by indirect immunofluorescence and electron spectroscopic imaging. Our results indicate that de novo chromatin condensation normally seen during mitos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 53 publications
3
91
1
5
Order By: Relevance
“…In this study, we found little evidence for chromatin condensation in nuclei treated with CaCl 2 at all KCl concentrations examined (0, 40 and 140 mM), supporting the notion that chromatin condensation may not be necessarily linked to or is independent of DNA degradation [45]. Previous studies have shown that histones are released in various apoptotic cells [46,47].…”
Section: Chromatin Structure In Isolated Nuclei Treated With Ca 2+supporting
confidence: 78%
“…In this study, we found little evidence for chromatin condensation in nuclei treated with CaCl 2 at all KCl concentrations examined (0, 40 and 140 mM), supporting the notion that chromatin condensation may not be necessarily linked to or is independent of DNA degradation [45]. Previous studies have shown that histones are released in various apoptotic cells [46,47].…”
Section: Chromatin Structure In Isolated Nuclei Treated With Ca 2+supporting
confidence: 78%
“…Activation of proteases and degradation of both the nuclear lamina and components of the intranuclear protein matrix enable aggregation of chromatin into apoptotic spherical bodies. 39 Furthermore, it is known that inhibition of lamin or nuclear scaffold degradation prevents nuclei from acquiring complete apoptotic features. 40,41 Whereas hyperphosphorylation of H2A.X in apoptotic cells depends indirectly on activation of caspases and nuclear scaffold (lamin) proteases, as shown in zVAD-(OMe)-fmk or zAPF-cmktreated cells, H1 dephosphorylation can be inhibited only by the caspase inhibitors zVAD-(OMe)-fmk and Ac-YVADcmk and not by the used nuclear scaffold protease inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…(58,59) Chromatin aggregation (23) may facilitate or promote the DNA fragmentation (68,69) by specific apoptotic endonucleases. Indeed, it has been recently shown that chromatin aggregation precedes oligonucleosomal fractionation (70) and that DNA is supercoiled in apoptotic chromatin. (71) Despite all this, the reason(s) why or how anthracyclines exert their preferential killing of tumor versus non-carcinogenic cells are still not well understood.…”
Section: Introductionmentioning
confidence: 99%